Secondhand smoke exposure and its role in the pathogenesis of preeclampsia: a narrative review of molecular and epidemiological perspectives - Yenny Febriany; Irfannuddin; Mohammad Zulkarnain; Yusuf Effendi (Published by Universitas Gadjah Mada, 2025)
Preeclampsia (PE) is a pregnancy complication characterized by hypertension after 20 wk of gestation, often accompanied by proteinuria or organ dysfunction. This condition is linked to genetic, environmental factors, and exposure to secondhand smoke (SHS). This study explores the relationship between SHS exposure and PE risk through a narrative literature review. Epidemiological and molecular studies data demonstrate that SHS exposure increases PE risk via oxidative stress, inflammation, and angiogenic disruptions. The analysis reveals that SHS exposure enhances reactive oxygen species (ROS) production, triggers systemic inflammation through the NF-κB pathway, and impairs angiogenic function by lowering the PlGF/sFlt-1 ratio. The risk significantly increases with exposures ≥2 hr/d or weekly frequencies ≥4 d, particularly in poorly ventilated domestic and occupational settings. Biomarkers such as cotinine and carbon monoxide (CO) are employed to assess exposure levels, providing robust evidence that duration and intensity of exposure are pivotal in PE pathogenesis. These findings highlight the importance of preventive strategies, including smoking bans, public health education, and integration of biomarker-based assessments into prenatal care. Future research should aim to clarify the molecular and epigenetic mechanisms involved and explore therapeutic interventions to mitigate SHS-induced damage.